Comunicación: profesión de la cultura - Restrepo, Mariluz (Organicom, 2004)
The author reflects on the role of communication professionals, focusing their relationship with the culture in a postmodern environment, one of new media and of creation and re-creation of symbols and postures. A new dimension is revealed to this professional, permitting the rise of other communicational processes, displacing those which are merely informational and instrumental in order to reinforce human communication, confronting versions, presenting new worlds and possibilities, showing and building culture above all.